Surface Proteins and Pneumolysin of Encapsulated and Nonencapsulated Streptococcus pneumoniae Mediate Virulence in a Chinchilla Model of Otitis Media - Keller, Lance E.; Bradshaw, Jessica L.; Pipkins, Haley; McDaniel, Larry S. (Frontiers in Cellular and Infection Microbiology, 2016)
Streptococcus pneumoniae infections result in a range of human diseases and are responsible for almost one million deaths annually. Pneumococcal disease is mediated in part through surface structures and an anti-phagocytic capsule. Recent studies have shown that nonencapsulated S. pneumoniae (NESp) make up a significant portion of the pneumococcal population and are able to cause disease. NESp lack some common surface proteins expressed by encapsulated pneumococci, but express surface proteins unique to NESp. A chinchilla model of otitis media (OM) was used to determine the effect various pneumococcal mutations have on pathogenesis in both NESp and encapsulated pneumococci. Epithelial cell adhesion and invasion assays were used to examine the effects in relation to deletion of intrinsic genes or expression of novel genes. A mouse model of colonization was also utilized for comparison of various pneumococcal mutants. It was determined that pneumococcal surface protein K (PspK) and pneumolysin (Ply) affect NESp middle ear pathogenesis, but only PspK affected epithelial cell adhesion. Experiments in an OM model were done with encapsulated strains testing the importance of native virulence factors and treatment of OM. First, a triple deletion of the common virulence factors PspA, PspC, and Ply, (ΔPAC), from an encapsulated background abolished virulence in an OM model while a PspC mutant had detectable, but reduced amounts of recoverable bacteria compared to wildtype. Next, treatment of OM was effective when starting antibiotic treatment within 24 h with resolution by 48 h post-treatment. Expression of NESp-specific virulence factor PspK in an encapsulated strain has not been previously studied, and we showed significantly increased adhesion and invasion of human epithelial cells by pneumococci. Murine colonization was not significantly increased when an encapsulated strain expressed PspK, but colonization was increased when a capsule mutant expressed PspK. The ability of PspK expression to increase colonization in a capsule mutant despite no increase in adhesion can be attributed to other functions of PspK, such as sIgA binding or immune modulation. OM is a substantial economic burden, thus a better understanding of both encapsulated pneumococcal pathogenesis and the emerging pathogen NESp is necessary for effective prevention and treatment.